Paper prototyping the fast and easy way to design and refine user interfaces - Snyder, Carolyn (San Diego, CA : Morgan Kaufmann Pub., 2003)
Do you spend a lot of time during the design process wondering what users really need? Do you hate those endless meetings where you argue how the interface should work? Have you ever developed something that later had to be completely redesigned? Paper Prototyping can help. Written by a usability engineer with a long and successful paper prototyping history, this book is a practical, how-to guide that will prepare you to create and test paper prototypes of all kinds of user interfaces. You'll see how to simulate various kinds of interface elements and interactions. You'll learn about the practical aspects of paper prototyping, such as deciding when the technique is appropriate, scheduling the activities, and handling the skepticism of others in your organization. Numerous case studies and images throughout the book show you real world examples of paper prototyping at work. Learn how to use this powerful technique to develop products that are more useful, intuitive, efficient, and pleasing: * Save time and money - solve key problems before implementation begins * Get user feedback early - use it to focus the development process * Communicate better - involve development team members from a variety of disciplines * Be more creative - experiment with many ideas before committing to one *Enables designers to solve design problems before implementation begins *Five case studies provide real world examples of paper prototyping at work *Delves into the specifics of what types of projects paper prototyping is and isn't good for.
Case studies -- Thinking about prototyping -- Making a paper prototype -- Planning a usability study with a paper prototype -- Task design -- Preparing the prototype -- Introduction to usability test facilitation -- Usability testing with a paper prototype -- Observers -- Data : capturing, prioritizing, and communicating -- What paper is (and isn't) good for -- The politics of paper prototyping -- When to Use paper -- Examples of user-centered design.
Includes bibliographical references (p. 355-360) and index.
Keywords: Prototypes, Engineering; Electronic books